Morphological and Soil Determinants of Forest Cover Changes in Świętokrzyski National Park and Its Buffer Zone in the last 200 Years - Ciupa, Tadeusz; Suligowski, Roman; Wałek, Grzegorz (Quaestiones Geographicae, 2015)
The research described in the paper utilized GIS methods and comparative cartography in order to analyze changes in forest cover in the period 1800-2011 in the Świętokrzyski National Park (76.26 km²) and its buffer zone (207.86 km²). The research was done for predefined elevation intervals, slope gradients, and genetic soil types. Source materials included historical maps as well as a digital elevation model. Changes in forest cover were noted in spatial and temporal terms and were usually linked to morphology and soil type. While the 19th century was characterized by intense deforestation, this process reversed starting in the early 20th century. Nevertheless, forest cover in the study area has still not returned to its state from 1800.